Glycemia monitoring: The problem of exogenous insulin input - Basov, I.; Meilūnas, M.; Švitra, D. (Mathematical Modelling and Analysis, 1999)
We present the system of two nonlinear difference‐differential equations with lag which is a mathematical model of self‐regulation of sugar level in blood. We analyze the pathological case, i.e. describe the concrete patients glycemia self‐regulation system and diet. The model helps to determine the dosage and tactics of the traditional insulinotherapy practicing discrete inputs of insulin into the organism with the help of injections.Glikemijos monitoringas: insultinio įvedimo uždavinysSantrauka. Darbe nagrinėjamas cukraus kiekio kraujyje savireguliacijos matematinis modelis. Jis aprašomas dviejų netiesinių diferencialinių‐skirtumų lygčių su vėluojančiu argumentu sistema. Nagrinėjama konkrečių pacientų glikemijos savireguliacijos sistema. Matematinis modelis leidžia nustatyti insulino dozę ir režimą, kai naudojame tradicinę insulino terapiją. Pateikti skaičiavimų rezultatai, iliustruojantys kelis ligos ir maitinimosi režimus.First Published Online: 14 Oct 2010